PERANCANGAN BUKU GLOBAL WARMING UNTUK SISWA SEKOLAH DASAR - M RIDHO PAHLEVI, Drs. Syafwan, M.Si., Dra. Jupriani, M.Sn (DEKAVE : Jurnal Desain Komunikasi Visual, 2018)
Global Warming is an increase in the average temperature of the earth's surface due to the erosion of the ozone layer and the greenhouse effect. General knowledge about global warming should be known by every layer of the age including children. Therefore, it is important to introduce global warming through books to children from an early age. Children prefer half or full pictures with clear instructions. The illustration books are expected to engender interest in reading to elementary school children and can stimulate creativity to elementary school children visually.Theories used in the design of the global warming book are global warming theory, visual communication design theory, child psychology theory and illustration theory. The design method used is 5W + 1H approach ie what, who, when, where, why, and how. The program used to create the illustration book is coreldraw. This illustration book is supported by the main media illustration book containing 20 pages and supporting media such as t-shirts, stickers, pins, x banner, totebags, crayons, notebooks and bookmarks.Kata kunci : Global Warming, Buku Ilustrasi